Exploring the Activation Mechanism of the mGlu5 Transmembrane Domain - Lans, Isaias; Díaz, Óscar; Dalton, James A. R.; Giraldo, Jesús (Frontiers in Molecular Biosciences, 2020)
As a class C GPCR and regulator of synaptic activity, mGlu5 is an attractive drug target, potentially offering treatment for several neurologic and psychiatric disorders. As little is known about the activation mechanism of mGlu5 at a structural level, potential of mean force calculations linked to molecular dynamics simulations were performed on the mGlu5 transmembrane domain crystal structure to explore various internal mechanisms responsible for its activation. Our results suggest that the hydrophilic interactions between intracellular loop 1 and the intracellular side of TM6 have to be disrupted to reach a theoretically active-like conformation. In addition, interactions between residues that are key for mGlu5 activation (Tyr6593.44 and Ile7515.51) and mGlu5 inactivation (Tyr6593.44 and Ser8097.39) have been identified. Inasmuch as mGlu5 receptor signaling is poorly understood, potentially showing a complex network of micro-switches and subtle structure-activity relationships, the present study represents a step forward in the understanding of mGlu5 transmembrane domain activation.